The Internationalization of Research in Europe. A Quantitative Study of 11 National Systems from a Micro-Level Perspective - Kwiek, Marek (My University, 2015)
This paper focuses on the impact of international research cooperation on individual research productivity in 11 European countries. Research productivity and international publication co-authorship of “internationalists” and “locals” (or academics collaborating and not collaborating internationally) are compared. The paper uses a micro-level (individual) approach and relies on the primary data collected in a comparable format through a survey from 17,211 European academics. In all countries and all clusters of academic fields studied, international collaboration in research is strongly correlated with substantially higher research productions. Cross-disciplinary and cross-country differences are discussed and policy implications are explored at individual and institutional levels.
Keywords: internationalization; research productivity; European universities; quantitative study; international collaboration; international co-authorship; CAP; EUROAC; academic productivity; predictors; knowledge production; research publications; academic publishing; productivity index; cross-national; comparative approach; academic profession; European academics; international publication patterns; academic stratification; internationals and locals; cosmopolitans; international research collaboration; productivity index; high research productivity; highly publishing academics; correlates of productivity; correlations